Comparison of supermarket and traditional market supply vegetable farmers of two districts of India (SAARC Journal of Agriculture, 2014)
The study was done on the economic analysis of tomato, brinjal and bhendi cultivation with a comparison of income, access to technology of supermarket and traditional market supply farmers in the two selected districts. The per hectare cost of cultivation of the three selected vegetables on supermarket and traditional market supply farms revealed that cost of cultivation of vegetables was remarkably higher for traditional farms than supermarket supplying farms. This was mainly due to excessive use of manures and fertilizers, irrigation, plant protection chemicals and human labour. The returns per rupee invested have been noted higher for supermarket supply farmers than that of traditional farmers. The evidence indicates that innovative institutions contribute in reducing production cost and augmenting farm profits. Discriminant function analysis shows that price, manures and fertilizers, yield, hired labour and net income contributed mostly to discriminate between two groups viz., supermarket and traditional market supplying farmers. DOI: http://dx.doi.org/10.3329/sja.v10i2.18333 SAARC J. Agri., 10(2): 121-136 (2012)